G‐C3N4‐Based Heterostructured Photocatalysts. Issue 3 (21st September 2017) - Fu, Junwei; Yu, Jiaguo; Jiang, Chuanjia; Cheng, Bei
Abstract: Photocatalysis is considered as one of the promising routes to solve the energy and environmental crises by utilizing solar energy. Graphitic carbon nitride (g‐C3 N4 ) has attracted worldwide attention due to its visible‐light activity, facile synthesis from low‐cost materials, chemical stability, and unique layered structure. However, the pure g‐C3 N4 photocatalyst still suffers from its low separation efficiency of photogenerated charge carriers, which results in unsatisfactory photocatalytic activity. Recently, g‐C3 N4 ‐based heterostructures have become research hotspots for their greatly enhanced charge carrier separation efficiency and photocatalytic performance. According to the different transfer mechanisms of photogenerated charge carriers between g‐C3 N4 and the coupled components, the g‐C3 N4 ‐based heterostructured photocatalysts can be divided into the following categories: g‐C3 N4 ‐based conventional type II heterojunction, g‐C3 N4 ‐based Z‐scheme heterojunction, g‐C3 N4 ‐based p–n heterojunction, g‐C3 N4 /metal heterostructure, and g‐C3 N4 /carbon heterostructure. This review summarizes the recent significant progress on the design of g‐C3 N4 ‐based heterostructured photocatalysts and their special separation/transfer mechanisms of photogenerated charge carriers. Moreover, their applications in environmental and energy fields, e.g., water splitting, carbon dioxide reduction, and degradation of pollutants, are also reviewed. Finally, some concluding remarks and perspectives on the challenges and opportunities for exploring advanced g‐C3 N4 ‐based heterostructured photocatalysts are presented. Abstract : g‐C3 N4 ‐based heterostructured photocatalysts have become research hotspots for their greatly enhanced charge carrier separation efficiency and photocatalytic performance. g‐C3 N4 ‐based conventional type II heterojunction, g‐C3 N4 ‐based Z‐scheme heterojunction, g‐C3 N4 ‐based p–n heterojunction, g‐C3 N4 /metal heterostructure, and g‐C3 N4 /carbon heterostructure have been widely reported in recent years. This review summarizes the design principles, preparation methods, charge transfer mechanism, and photocatalytic applications of these g‐C3 N4 ‐based heterostructured photocatalysts.